(3GdNUGFU GdfHhjI GdcHQis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3eMeO GdSYjO Hf YeQ Hf CMeO Hf eMeO GdMSfj s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CWdY aj SeGA GdfHhI SQGLkG dGeYkG s
(3BNQgG (B:s
(3hUdi Gddg Ydji SjOfG eMeO hBdg hUMHg hSde hGdMeO ddg QH GdYGdejf fLRJ GdNUGFU GdcHQi hGdoeYLRGJ GdfHhjI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B146 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B181 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B159 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs